Stalled Village Democracy: Analyzing the Role of Village Consultative Bodies (BPD) in the Formulation of Local Regulations - Syafiuddin, Syafiuddin; Nadir , Nadir; Wardani, Win Yuli; Pakendek, Adriana (Jurnal Ilmu Hukum Kyadiren, 2026)
The Village Consultative Body (BPD) plays a pivotal role in formulating Village Regulations (Perdes), holding strategic importance in fostering participatory and democratic village governance. Nevertheless, in practice, legislative awareness among BPD members remains limited, and community participation in the process is minimal. This study examines the effectiveness of the BPD’s legislative authority in the formulation of Village Regulations, with a focus on members’ legislative awareness, community involvement, and the structural and cultural barriers they face. Employing a juridical-sociological approach and descriptive qualitative methods, the research was conducted in three villages within Tlanakan District, Pamekasan Regency. The findings reveal that the BPD tends to be passive, often co-opted by the authority of the Village Head, and unable to exercise its legislative function independently and substantively. Community participation is largely symbolic, hindered by low regulatory literacy. The study concludes that strengthening institutional capacity and reforming local power dynamics are crucial to ensuring accountable village legislation.